2015
DOI: 10.1186/s12885-015-1544-y
|View full text |Cite
|
Sign up to set email alerts
|

High basal Wnt signaling is further induced by PI3K/mTor inhibition but sensitive to cSRC inhibition in mammary carcinoma cell lines with HER2/3 overexpression

Abstract: BackgroundElevated basal, ligand-independent, Wnt signaling in some canine breast cancer cells is not caused by classical mutations in APC, β-Catenin or GSK3β but, at least partially, by enhanced LEF1 expression. We examined the expression and function of EGFR/HER-regulated pathways on the ligand-independent Wnt signaling.MethodsTwelve canine mammary tumor cell lines with previously reported differential basal Wnt activity were used. The expression levels of genes related to EGF-signaling were analyzed by clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 58 publications
3
36
1
Order By: Relevance
“…The TKI Src‐I1, which is an inhibitor of cSRC, also decreased cell proliferation but only at a rather high concentration (20 μM) of Src‐I1 . According to Bain et al , the IC50 value of Src‐I1 is approximately 0.18 μM, which is far below the concentration that we used . Therefore, we investigated a panel of related TKIs to find a connection between cSRC, Wnt and EGFR signalling.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The TKI Src‐I1, which is an inhibitor of cSRC, also decreased cell proliferation but only at a rather high concentration (20 μM) of Src‐I1 . According to Bain et al , the IC50 value of Src‐I1 is approximately 0.18 μM, which is far below the concentration that we used . Therefore, we investigated a panel of related TKIs to find a connection between cSRC, Wnt and EGFR signalling.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, we investigated the underlying cause of the high basal Wnt activity in the CMT‐U27 metastatic canine mammary cell line, which was selected from a panel of canine mammary cell lines where 3 out of 12 cell lines were characterized by high ligand‐independent Wnt signalling . Additional studies showed that these cell lines had HER2 /3 overexpression, absent PTEN mRNA , and sensitivity to Src‐I1, indicating a possible relationship between HER signalling and Wnt activity . However, in the present study, we were unable to show a direct relation by silencing HER protein expression with siRNAs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations